2017
DOI: 10.1097/txd.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Association of Body Mass Index With Overall Survival Outcomes After Liver Transplantation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
1
8
0
2
Order By: Relevance
“…Since the influence of obesity on overall survival post-LT is controversially discussed ( 14 , 15 ), we first focused on donor BMI as a potential risk factor to impact liver graft quality. Recently, we illustrated that the natural cytotoxicity receptor NKG2D is a marker of renal senescence and correlates with allograft function ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the influence of obesity on overall survival post-LT is controversially discussed ( 14 , 15 ), we first focused on donor BMI as a potential risk factor to impact liver graft quality. Recently, we illustrated that the natural cytotoxicity receptor NKG2D is a marker of renal senescence and correlates with allograft function ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of 115 473 patients who underwent liver transplant, recipients with BMI between 25 and 40 kg/m 2 had lower mortality risk compared to their normal weight counterparts; however, the best post‐liver transplant survival was observed in patients with the moderate body weight excess (BMI of 28 to 37 kg/m 2 ), indicating a nonlinear relationship between BMI and post‐liver transplant survival. Stratification by the MELD score, showed a higher BMI was related to improved survival in patients with MELD 19 to 25; with no association between BMI and MELD in patients with scores >25 18 . Despite longer hospitalisation and shorter survival in patients on either extreme of BMI (<18.5 kg/m 2 or >40 kg/m 2 ), liver transplant in extremely obese patients with lower MELD scores (≤22) considerably enhanced patient survival 12 .…”
Section: Methodsmentioning
confidence: 98%
“…Using CT estimates of muscle mass, DiMartini et al found that 62% of pre-transplant patients with a BMI >25 (including both overweight and obese patients) were simultaneously sarcopenic, while 80% of cirrhotic patients with a "normal" BMI of 18.5-25 were also sarcopenic (21). In a retrospective analysis of 48,226 patients who had undergone liver transplant between 2002 and 2013 (Organ Procurement and Transplantation Network database), Chang et al reported best survival outcomes for patients with a BMI of 28-37, even after stratifying for MELD score, suggesting that patients listed for transplant may do better if they are able to maintain some of their BMI weight in the pre-transplant period (22). Moreover, they found that the relationship between BMI and mortality after transplant was "U"-shaped, with highest mortality risk at the extremes of BMI (<19 and >40), with a nadir (least mortality) at a BMI of 34.…”
Section: Post-transplant Outcomesmentioning
confidence: 99%